2016
DOI: 10.1128/aac.03105-15
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Association between Polymorphisms in the RING E3 Ubiquitin Protein Ligase Gene and Ex Vivo Susceptibility to Conventional Antimalarial Drugs in Plasmodium falciparum Isolates from Dakar, Senegal

Abstract: The RING E3 ubiquitin protein ligase is crucial for facilitating the transfer of ubiquitin. The only polymorphism identified in the E3 ubiquitin protein ligase gene was the D113N mutation (62.5%) but was not significantly associated with the 50% inhibitory concentration (IC 50 ) of conventional antimalarial drugs. However, some mutated isolates (D113N) present a trend of reduced susceptibility to piperaquine (P ‫؍‬ 0.0938). To evaluate the association of D113N polymorphism with susceptibility to antimalarials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…The difference between clones and field parasites may induce differences between in vitro development of mutations and reduced susceptibility and wild isolates showing different patterns of gene sequence regulation and expression. There was no significant difference in the proportion of parasites with decreased susceptibility to PPQ between the D113 wild-type and the mutated 113N P. falciparum strains in contrary to previous findings [ 16 ].…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The difference between clones and field parasites may induce differences between in vitro development of mutations and reduced susceptibility and wild isolates showing different patterns of gene sequence regulation and expression. There was no significant difference in the proportion of parasites with decreased susceptibility to PPQ between the D113 wild-type and the mutated 113N P. falciparum strains in contrary to previous findings [ 16 ].…”
Section: Resultscontrasting
confidence: 99%
“…Previous studies showed that P. falciparum strains carrying the 113N mutant allele for the E3 ubiquitin-protein ligase gene were less susceptible ex vivo to CQ and DQ, and that all the Senegalese isolates with reduced susceptibility to PPQ were mutants [ 15 , 16 ]. Although the D113N mutation was found in a large number of samples (n = 147, 68.4%), this mutation was not found to be involved in the susceptibility modulation to common anti-malarial drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these data suggest that Pfpm2 is not the only gene involved in PPQ resistance in Africa. Other genes must be studied, such as the RING E3 ubiquitin protein ligase gene (42) ex vivo PPQ resistance (44,45), but new mutations in this gene, such as H97Y, F145I, M343L, or G353V, could also be involved (25,35).…”
mentioning
confidence: 99%
“…The IHU-Méditerranée Infection participates in identification, development and/or validation of new molecular resistance markers to doxycycline ( pfmdt and pftetQ ) [59] , [60] , [61] , [62] , quinine ( pfnhe-1 ) [63] , artemisinin ( pfK13 ) [64] , [65] , [66] , [67] , [68] and quinolines ( pfmdr1, pfmdr2, pfmdr5, pfmdr6, etc.) [69] , [70] , [71] , [72] .…”
Section: Chemoprevention Of Malariamentioning
confidence: 99%